العلاقات اللبية الجزائرية خلال الثورة الجزائرية 1954-1962م وانعكاساتها - مسعودي، أميرة, ابراهيمي، عفاف (جامعة الوادي University of eloued, 2018)
"ان الدارس لموضوع العلاقات الليبية خلال الثورة التحريرية سيكتشف حتما اهميتها الاستراتيجية في دعم الثورة التحريرية 1954م- 1962م انطلاقا من الموقف الحكومي والشعبي المتميز الذي اتخذته اتجاه الثورة التحريرية والمدعم للقضية الجزائرية من مختلف النواحي إن كان عربيا أو إفريقيا أو حتى على مستوى هيئة الأمم المتحدة. كما كانت تمثل منبرا لإسماع صوت الثورة الجزائرية عبر جهازها الاعلامي وذلك لفضح جرائم الاستعمار الفرنسي، كما شكلت ليبيا منطقة عبور المساعدات العسكرية باعتبارها قاعدة خلفية من الجهة الشرقية، لذلك كانت ليبيا جديدة الحرص دائما على تلبية المطالب الجزائرية وسعيها لتوفير الظروف المساعدة لتأمين نشاطهم وتحركاتهم، غير أن هذه العلاقات الطبية كانت لها انعكاسات على الثورة التحريرية إيجابية من ناحية وسلبية من ناحية أخرى، إلى درجة القيام بمشاريع التقسيم وإنشاء الخطوط المكهربة على الحدود لمنع إيصال الأسلحة إلى الجزائر، لكن رغم هذا كله لا يمكن إهمال الجانب الايجابي لهذه العلاقات والذي تمثل في المقاطعة الاقتصادية للبضائع الفرنسية، بالإضافة إلى نجاح ليبيا في تغيير وجهة نظر العديد من الدول لصالح القضية الجزائرية كتركيا والاتحاد السوفياتي. " "The student of the Libyan relations during the liberation revolution will inevitably discover its strategic importance in supporting the liberation revolution from 1954 to 1962, based on the distinguished governmental and popular position taken by the revolutionary and supporting revolution of the Algerian cause in various aspects, whether Arab, African or even at the level of the United Nations. It also represented a platform for the voice of the Algerian revolution through its media apparatus in order to expose the crimes of French colonialism. Libya also formed the transit area of military aid as a rear base on the eastern side, so Libya was always keen to meet the Algerian demands and its efforts to provide the necessary conditions to secure their activities and movements. That these medical relations have had repercussions on the liberation revolution on the one hand and negative on the other, to the extent of the projects of division and the establishment of electric lines on the border to prevent the delivery of weapons to Algeria, but despite all this can not be neglected elves Which is represented in the economic boycott of French goods, in addition to the success of Libya in changing the view of many countries in favor of the Algerian cause, such as Turkey and the Soviet Union. "
مدكرة ماستر تاريخ تخصص تاريخ المغرب العربي الحديث والمعاصر
Keywords: العلاقات اللبية الجزائرية، الثورة الجزائرية; Libyan - Algerian relations, Algerian revolution; Libyan - Algerian relations, Algerian revolution